The nature and function of talent identification in junior-elite football in English category one academies - Reeves, M. J.; Littlewood, M. A.; McRobert, A. P.; Roberts, S. J. (Soccer & Society, 2018)
The focus of this study was to examine the nature and function of talent identification in category one football academies in the UK. Data were collected from three participant groups: heads of recruitment (n = 12), recruitment staff (n = 18) and scouts (n = 7). Data were collected by means of semi-structured interviews, conducted either face-to-face or via Skype®. Four themes emerged from the data: (1) league structures in junior grassroots football; (2) reflective practice; (3) looking at the whole player; and (4) luck. The paper concludes by suggesting that there are issues that need to be considered by the football association, county football associations and clubs. Those issues include the organization of leagues in junior football, the education of scouts and recruitment staff around reflective practice and understanding how to identify psycho-social attributes whilst identifying talent.